The Association between Project Management Knowledge Areas and Sustainable Outcomes in Urban Construction Projects - Jafarimand, Jahed (European Journal of Sustainable Development, 2018)
The sustainable urban development is a critical component of urban planning, aiming to improve the urban development efficiency, increase quality of life, protect the ecological environment of the city and realize the sustainable utilization of urban resources. As part of the strategy for sustainable urbanization, several urban construction projects has been implemented in some cities of Iran for years. To evaluate the effectiveness and reveal the future direction of development of these projects, it is essential to analyze their management structure in the framework of sustainable development. This paper investigated the relation between project management knowledge areas (PMKA) and the expected sustainable outcomes of the projects from four urban construction projects in Tabriz, Iran. Through a quantitative research method including data analysis using Chi-square and Cramer’s V association, different sorts of link between 10 PMKA and 11 expected sustainable outcomes of the urban construction projects were revealed and discussed. Keywords: Management, Project, Sustainability, Urbanization.